Assessment of spontaneous resolution of idiopathic bone cavity (Journal of Applied Oral Science, 2022)
Idiopathic Bone Cavity (IBC) or Simple Bone Cyst (SBC) is a non- epithelialized bone cavity with serosanguinous fluid content or empty. There is a literature debate regarding its pathogenesis that remains unclear. The main treatment option is the surgical exploration, although there are successful cases described in the literature in which just a follow-up with clinical and radiographic evaluation was performed. Objective: This study aimed to assess the spontaneous resolution of idiopathic bone cavity untreated by surgery. Material and Methods: Twenty-one patients diagnosed with surgically untreated IBC were submitted to a follow-up protocol modified from Damante, Guerra, and Ferreira5 (2002). A clinical and radiographic evaluation was performed in 13 patients (13/21), while eight patients (8/21) were only radiographically evaluated. Three observers evaluated the panoramic radiographs of 21 patients and the Kappa test was performed by intra and inter-examiners. Inductive and descriptive statistics were applied to the results. Results: Only one patient had a positive response to palpation and percussion of the teeth in the cyst area. Most of the cysts evaluated were rated as 3 (lesion “in involution”), 4 (lesion “almost completely resolved”), or 5 (“completely resolved”). Conclusions: We observed progressive spontaneous resolution of IBC. Most cysts were found in the recovery process in different follow-up periods. Patient's follow-up, without surgery, may be considered after the diagnosis based on epidemiological, clinical, and radiographic features of the lesion.